In silico recombinant plasmid design of pHA171 with phdABCD insertion for ethidium bromide degradation - Muhammad Ilham Fahri; Rabiah Musfira Alatiffa; Sania Isma Yanti; Indira Prakoso; Alysha Naomi Mashitah (Acta Biochimica Indonesiana, 2021)
Background: Ethidium bromide is a common reagent that is used in nucleic acid staining. However, ethidium bromide has toxic and carcinogenic properties that are harmful to the environment. Phenanthrene dioxygenase (encoded by phdA, phdB, phdC, and phdD genes) in Nocardioides sp. KP7 can oxidize the phenanthridine structure aim to eliminate carcinogenic properties. Objective: This study aims to visualize and predict the structure, active site, and characteristics of the phenanthrene dioxygenase using bioinformatics tools. Methods: Plasmid design were prepared by inserting genes of interest phdA, phdB, phdC, and phdD from the NCBI database. Furthermore, several protein analysis tools were used for structure visualization, active site enzyme improvement, and protein characteristic of phenanthrene dioxygenase. Results: The prediction results found that phenanthrene dioxygenase reacts with the ethidium bromide substrate through the interaction of Fe3+ ions with water. The solubility level of phenanthrene dioxygenase protein is 0.404, suggesting that the protein has low solubility. The protein isoelectric point (pI) is between 5.17 to 5.36, and the protein molecular weight is 121.143 kDa. Conclusion: In silico analysis has supported that recombinant plasmid met characteristics for the construct which consists of gene interest and protein library.